A theory of legal punishment : deterrence, retribution, and the aims of the state - Altman, Matthew C. (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book argues for a mixed view of punishment that balances consequentialism and retributivism. He has published extensively on philosophy and applied ethics. A central question in the philosophy of law is why the state's punishment of its own citizens is justified. Traditionally, two theories of punishment have dominated the field: consequentialism and retributivism. According to consequentialism, punishment is justified when it maximizes positive outcomes. According to retributivism, criminals should be punished because they deserve it. This book defends a mixed view that recognizes the strength of both of these intuitions. By this account, the legislature should develop institutional policies and statutory penalties that maintain the social order, that is, consequentialism. It establishes punishment policies to deter criminal activity. By contrast, the criminal judiciary should give individual defendants what they deserve, that is, retributivism and thus expressing the community's appropriate sense of resentment at being wronged. The book justifies the two-tiered model by showing how it accords with our moral intuitions, our assumptions about how what we know affects our moral obligations, and a commonly held theory of freedom. This approach is developed by engaging classic and contemporary work in the philosophy of law, and shows its advantages over competing approaches from contemporary retributivists and other mixed theorists. The work also defends consequentialism against a longstanding objection that the social sciences give us little guidance regarding which policies to adopt. It draws on cutting-edge criminological research to show how punishment theory can help us to address some of our most pressing social issues, including the death penalty, drug laws, and mass incarceration. The book will also be of interest to legal philosophers, social scientists, especially criminologists, sociologists, economists, and political scientists"--
Crimes and burdens -- Preserving the public order : a defense of consequentialism -- The rational and the reasonable -- Expressing resentment : a defense of retributivism -- The two-tiered model of punishment -- The epistemic argument -- The compatibilist argument -- The moral argument -- In defense of criminology -- On proportionality -- Jury nullification and reflective equilibrium -- Consequences of capital punishment -- Retribution and restorative justice -- Conclusion.
OCLC-licensed vendor bibliographic record.
Keywords: Punishment -- Philosophy; Criminal law -- Philosophy; Punishment in crime deterrence; Lex talionis; LAW / General; LAW / Criminal Law / General; LAW / Jurisprudence